Optimization of some processing parameters and quality attributes of fried snacks from blends of wheat flour and brewers' spent cassava flour. Issue 1 (29th July 2015) - Omidiran, Adebukola T.; Sobukola, Olajide P.; Sanni, Ajoke; Adebowale, Abdul‐Rasaq A.; Obadina, Olusegun A.; Sanni, Lateef O.; Tomlins, Keith; Wolfgang, Tosch
Abstract: The effect of some processing parameters (frying temperature [140–160°C], frying time [2–4 min], level of brewers' spent cassava flour (BSCF) [20–40%], and thickness [2–4 mm]) on some quality attributes of wheat‐BSCF fried snack was investigated. Response surface methodology based on Box–Behnken design was used to optimize the effect of process parameters on product quality. Sensory evaluation of the optimized sample to determine its level of acceptability was carried out as well as the comparison with fried snack from 100% wheat flour. Increasing temperature had significant ( P < 0.05) negative effect on the texture. Based on the desirability (0.771) concept, a frying temperature of 140 °C, frying time of 4 min, 32% level of BSCF, and 2 mm thickness was obtained as the optimized conditions. Sensory analyses showed that the optimized sample was preferred in terms of texture and its oiliness to fried snack prepared from 100% wheat flour, but, the aroma, taste and appearance of the wheat snack were preferred. Abstract : Wheat flour and brewers' spent cassava flour were blended in the ratio 80:20, 70:30, and 60:40 with 100% whole flour of each. Response surface methodology based on Box–Behnken design was used to optimize the effect of process parameters on product quality of the fried snacks. Fried snacks from 100% Wheat flour had higher oil uptake than the optimized snacks and this is supported by the scanning electron micrographs of the fried snacks.